INCIDENTAL FINDING OF CONTRALATERAL BREAST CANCER IN CONTRALATERAL PROPHYLACTIC MASTECTOMY SPECIMEN: A CASE REPORT - Kosovac, Dimitrije; Suđecki, Branko; Kosovac, Olivera; Jevtić, Marko; Pupić, Gordana (HEALTH CARE, 2025)
Introduction/Aim: Prophylactic mastectomy may be performed in women with high genetic or familial risk, or unilaterally alongside therapeutic mastectomy. Although malignancy is not expected in prophylactic specimens, incidental contralateral breast cancer (CBC) may alter management and prognosis. The aim of this study is to present a clinical case of the incidental finding of contralateral breast carcinoma (CBC) in a tissue specimen obtained through contralateral prophylactic mastectomy (CPM) in a 46-year-old patient who had been initially diagnosed with ductal carcinoma in situ (DCIS) in the opposite breast. Case report: We report a 46-year-old woman initially diagnosed with ductal carcinoma in situ (DCIS) of the right breast. After declining adjuvant radiotherapy, she opted for bilateral nipple-sparing mastectomy with direct-to-implant reconstruction. Histopathology confirmed DCIS with a focal invasive component in the right breast and unexpectedly revealed three microscopic focuses of DCIS in the contralateral breast, alongside fibrocystic changes and atypical ductal hyperplasia. Discussion: The annual incidence of CBC is estimated at 0.5-0.75%. Examination of contralateral prophylactic mastectomy (CPM) specimens may uncover high-risk lesions (ADH, ALH, LCIS) or, rarely, invasive carcinoma. Such findings highlight the diagnostic potential of CPM and the importance of multidisciplinary evaluation when selecting candidates for risk-reducing surgery. Conclusion: Although CPM does not consistently improve overall survival, it can contribute to individualized risk reduction, simplified surveillance, and reduced anxiety in selected patients. This case underscores its diagnostic value in detecting occult contralateral malignancy and reinforces the need for personalized surgical planning within a multidisciplinary framework.